The Impact of Human Capital Investment on Labor Productivity in the Digital Era - Novegya Ratih Primandari; Jemi Pabisangan Tahirs; Muh. Nur; Jemadi Jemadi; Nuralam Nuralam (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine the impact of human capital investment on workforce productivity in the digital era. This research approach collects data through a literature review, involving reading literature from various sources including books, reports, articles, and journals using qualitative and deductive approaches. The results of this study indicate that human capital investment has a positive impact on the workforce, companies, and economic growth. At the individual level, this investment results in increased competitiveness, career mobility, job satisfaction, and income. For companies, a skilled workforce is a strategic asset for improving efficiency, quality, and innovation, while strengthening employee loyalty. At the macro level, quality human capital drives economic growth and national competitiveness. However, its implementation faces challenges such as high training costs, unequal access to education, resistance to change, and weak supporting policies. Therefore, a strategy is needed that includes cross-sector collaboration, the use of digital technology, upskilling and reskilling programs, and incentive policies to maximize the benefits of human capital investment